Role of MR-proADM and Monocyte CD169 in Predicting In-Hospital and 60-Day Mortality in COVID-19 Patients - Sergio Venturini; Daniele Orso; Francesco Cugini; Giovanni Del Fabro; Astrid Callegari; Ingrid Reffo; Danilo Villalta; Laura de Santi; Elisa Pontoni; Dina Giordani; Paolo Doretto; Chiara Pratesi; et al. (Clinical Pathology)
Objectives: Mid-regional pro-adrenomedullin (MR-proADM) and monocyte CD169 (CD169) are valuable prognostic indicators of severe COVID-19. Methods: We assessed the predictive ability of a single measurement of MR-proADM and CD169 at emergency department (ED) admission to forecast in-hospital and 60-day mortality in adult COVID-19 patients. We analyzed clinical and laboratory data, with in-hospital mortality as the primary endpoint and 60-day mortality as the secondary endpoint. We examined associations with clinical and laboratory variables through univariate and multivariate analyses. Results: Data from 382 patients over 14 months were analyzed. Significant predictors of in-hospital mortality included age ⩾ 70 years (hazard ratio [HR] 8.1; 95% confidence interval [CI] 2.2-29.5), CD169 ratio ⩾ 20 (HR: 2.4; 95%CI: 1.6-5.6), MR-proADM ⩾ 1.1 mmol/L (HR: 5.1; 95%CI: 1.7-15.6), the need for invasive mechanical ventilation (HR: 6.8; 95%CI: 2.4-19.1), and active cancer (HR: 5.2; 95%CI: 1.8-15.2). For 60-day mortality, only elevated MR-proADM levels showed predictive value (HR: 6.7; 95%CI: 1.7-25.0), while high serologic titer was protective (HR: 0.4; 95%CI: 0.1-0.9). Conclusion: A single MR-proADM and CD169 measurement upon ED admission has prognostic value for in-hospital mortality, with MR-proADM also predicting 60-day mortality.